2020
DOI: 10.7150/jca.39359
|View full text |Cite
|
Sign up to set email alerts
|

LZAP promotes the proliferation and invasiveness of cervical carcinoma cells by targeting AKT and EMT

Abstract: Objective: To explore the relationship and mechanism of LZAP in the occurrence and development of cervical cancer and to provide a new target and intervention method for the treatment of cervical cancer. Methods: Data mining and analysis of LZAP expression levels were performed using several online databases, including The Cancer Genome Atlas (TCGA). A cervical cancer cell line that stably overexpresses LZAP was established, and the effect of LZAP overexpression on cell proliferation, invasion, migration and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Accumulating evidence indicates that CDK5RAP3 has been implicated in governing cellular signal transduction including the p53 ( 2 , 15 ), NF-κB ( 5 , 8 , 9 , 48 ), Wnt ( 20 , 24 , 25 ), wild-type p53-induced phosphatase 1 (Wip 1) ( 10 , 33 ), AKT ( 27 , 30 ) and signal transducer and activator of transcription 3 (STAT3) signaling cascades ( 17 ). As previously described, CDK5RAP3 positively regulates p53 activity either in the presence or absence of ARF or independently of p53 mutation state ( 2 , 15 ).…”
Section: Biological Functions Of Cdk5rap3mentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulating evidence indicates that CDK5RAP3 has been implicated in governing cellular signal transduction including the p53 ( 2 , 15 ), NF-κB ( 5 , 8 , 9 , 48 ), Wnt ( 20 , 24 , 25 ), wild-type p53-induced phosphatase 1 (Wip 1) ( 10 , 33 ), AKT ( 27 , 30 ) and signal transducer and activator of transcription 3 (STAT3) signaling cascades ( 17 ). As previously described, CDK5RAP3 positively regulates p53 activity either in the presence or absence of ARF or independently of p53 mutation state ( 2 , 15 ).…”
Section: Biological Functions Of Cdk5rap3mentioning
confidence: 99%
“…The study from Zheng et al., also showed that CDK5RAP3 suppresses the inhibitory phosphorylation of GSK3β via inhibiting AKT phosphorylation in gastric cancer ( 25 ). Moreover, their group demonstrated that CDK5RAP3 modulates AKT signaling in both gastric neuroendocrine and cervical carcinoma ( 27 , 30 ). CDK5RAP3 also negatively regulates AKT/hypoxia inducible factor-1α (HIF-1α)/vascular endothelial growth factor A (VEGFA) pathway in gastric neuroendocrine carcinoma (GNEC) ( Figure 5D ).…”
Section: Biological Functions Of Cdk5rap3mentioning
confidence: 99%
See 2 more Smart Citations
“…Cervical squamous cell carcinoma (CSCC) is a common cancer; it is the fourth most frequently diagnosed cancer and fourth leading cause of cancer-related death in women ( 1 ). Although many novel treatment methods and technologies have been used in CSCC, the clinical outcomes of patients have not been satisfactory ( 2 ). Some studies have reported that the 5-year overall survival of CSCC patients is still less than 17% ( 3 ).…”
Section: Introductionmentioning
confidence: 99%